Knowledge of Medical Students regarding Antimicrobial Resistance - Zaid Al-Attar,; Saba Jassim,; Mohammed Anwar Abbood,; Wijdan Akram Hussein, (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
The discovery of antibiotics has enhanced the treatment outcomes of infectious diseases. Nevertheless, the injudicious use of antibiotics has triggered a global public health crisis and caused a worldwide spread of antimicrobial-resistant microorganisms. Antimicrobial resistance is slowly becoming a major health problem all around the world, especially in our country, and this might be due to the incorrect, unwise prescription of antimicrobial agents among some doctors, which gives rise to this problem. The present study aimed to estimate the knowledge of medical students in Baghdad regarding antimicrobial usage and resistance and to find the association of sociodemographic factors with knowledge scores. A descriptive cross-sectional study was conducted in six medical colleges in Baghdad. An online- based questionnaire was published and used in collecting the data. The data were reviewed and entered to be statistically analyzed in SPSS using the Chi-square test and were presented as frequencies, percentages, graphs and tables. The results showed that 44.1% of the studied sample had a fair knowledge of antimicrobial resistance. There was a statistical significance between gender and knowledge about antimicrobial resistance as the P-value was 0.006. In addition, there was a statistically significant association between the stage and the knowledge about antimicrobial resistance, where the P-value was (0.000). It was concluded that most of the participants had fair to good knowledge regarding antimicrobial resistance that was significantly associated with gender and stage.